2012
DOI: 10.1111/acel.12010
|View full text |Cite
|
Sign up to set email alerts
|

Aging leads to a programmed loss of brown adipocytes in murine subcutaneous white adipose tissue

Abstract: SUMMARY Insulin sensitivity deteriorates with age, but mechanisms remain unclear. Age-related changes in the function of subcutaneous white adipose tissue (sWAT) are less characterized than those in visceral WAT. We hypothesized that metabolic alterations in sWAT, which in contrast to epididymal WAT, harbors a sub-population of energy dissipating UCP1+ brown adipocytes, promote age-dependent progression towards insulin resistance. Indeed, we show that a predominant consequence of aging in murine sWAT is loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 43 publications
(41 reference statements)
11
123
3
Order By: Relevance
“…Because Ucp1 expression was increased modestly in the brown fat pads of Tg-4EBP1mt-muscle mice (Supplemental Figure 8, B and C), we investigated the fate of brown fat in more detail. Loss of "browning" in brown adipose tissue has been correlated with increasing age (56,57). At 17 months of age, we found marked white adipocyte infiltration in the brown fat pads of control mice.…”
Section: Resultsmentioning
confidence: 64%
“…Because Ucp1 expression was increased modestly in the brown fat pads of Tg-4EBP1mt-muscle mice (Supplemental Figure 8, B and C), we investigated the fate of brown fat in more detail. Loss of "browning" in brown adipose tissue has been correlated with increasing age (56,57). At 17 months of age, we found marked white adipocyte infiltration in the brown fat pads of control mice.…”
Section: Resultsmentioning
confidence: 64%
“…1f inset) 14 . In agreement, aging upregulates MAOA protein (Extended Data 2e) 15 . Collectively, these data suggested a link between reduced adipocyte lipolysis and elevated catecholamine catabolism machinery in ATMs during aging.…”
Section: Main Textmentioning
confidence: 53%
“…We and others have shown that GHS-R is highly expressed in hypothalamus, but its expression in peripheral tissues is very low in young mice. Intriguingly, circulating ghrelin and GHS-R expression in the brain and adipose tissues increase during aging [4,5]. We have reported in Aging Cell that old Ghsr-null mice are lean and insulin-sensitive, exhibiting a healthier metabolic profile similar to that of young animals [6].…”
Section: Ghrelin Receptor Controls Obesity By Fat Burning Yuxiang Sunmentioning
confidence: 98%
“…Beside the classical brown adipocytes present in BAT, brown-adipocyte-like "beige" cells residing in WAT also have thermogenic properties [3]. Aging is associated with programmed loss of "beige" cells [4]. Animal studies reveal that thermogenic activation in brown and beige adipocytes protects against obesity.…”
Section: Ghrelin Receptor Controls Obesity By Fat Burning Yuxiang Sunmentioning
confidence: 99%